Protocol for a systematic review on systemic and skin toxicity of important hazardous hair and nail cosmetic ingredients in hairdressers - Uter, Wolfgang; Johansen, Jeanne D.; Havmose, Martin S.; Kezic, Sanja; Van Der Molen, Henk F.; Macan, Jelena; Babic, Zeljka; Turk, Rajka; Symanzik, Cara; John, Swen M. (BMJ Open, 2021)
Introduction Hairdressers constitute a major subgroup in the service sector. They are exposed to various substances hazardous for skin, airways or systemically. Accordingly, skin and other occupational diseases are common. The present systematic review will compile and appraise evidence regarding skin, systemic and airways toxicity of an indicative set of specific, important product ingredients. Additionally, evidence concerning hand eczema morbidity among hairdressers will be reviewed. Methods and analysis Systematic searches will be performed in two electronic literature databases (Medline, Web of Science-Core Collection), the Cochrane register and two collections of toxicological dossiers (Scientific Committee on Consumer Safety of the European Commission and the MAK Commission of the German Research Council). Additional literature sources will be retrieved using hand search of reference lists of included studies and snowballing methods. We will include studies with all types of quantitative study designs, including results from in vitro and in vivo experiments, chemical analysis, epidemiological findings and clinical results. We will assess the risk of bias within studies amalgamating an abbreviated version of the Mixed Methods Appraisal Tool, basic Cochrane criteria and US Environmental Protection Agency assessment factors for scientific information. As we expect large heterogeneity in methods and outcomes, we will conduct a narrative synthesis of results instead of a meta-analysis, except where quantitative pooling is feasible. Ethics and dissemination Ethical approval and patient consent are not required as this is a systematic review based on published studies. The results of this study will be published in international peer-reviewed journals. PROSPERO registration number CRD42021238118
CRIS-Team WoS Importer:2021-12-17